A study on customer behaviors in chain coffee shops in Vietnam - Nguyễn, Hữu Cường (2020)
This research aims toinvestigate and understand the relationship between price, customer-based brand equity, customer satisfaction, and brand loyalty in the Vietnam’s chain coffee shops. The chain coffee shops are earning big money and growing fast in Vietnam so thatit is necessary to appreciate the importance of customer behaviorsto manage this type of business. To do that, we set brand loyalty and customer satisfaction as dependent variables and set price, congruence, and quality as independent variables then describe the difference of those relationships in two empirical cases in Hanoi and Ho Chi MinhCity. We usethequantitative approach on a sample of 427 respondents in Highlands Coffee and The Coffee House,which are two majorVietnamese coffee shop brands. We utilize the structural equation modeling (SEM) method by SPSS software. Descriptive analyses and path analyses of the multivariate regression model support the validityof the proposedmodel. The findings in this studyare thatsignificant positive effects from price, quality, and congruence on customer satisfaction and satisfaction on brand loyalty in Hanoi and Ho Chi MinhCity chain coffee shops. The analysesalso indicatethat among three antecedents of customer satisfaction, quality has the most substantial influence, follow by congruence and price. Moreover, the analyses tellthat in Ho Chi MinhCity, customer satisfaction has much higher impacton brand loyalty than in Hanoi. Several implications might be withdrawn to coffee shop brands as a consequence of these results